Analisis Value Chain Pembiayaan Bank Muamalat Indonesia - Syarif Mumtaza Fahmi (JURNAL ILMIAH EDUNOMIKA, 2024)
In the era of increasing competition within Indonesia's Islamic banking industry, PT Bank Muamalat Indonesia, as the first Islamic bank, faces significant challenges in maintaining market share and improving its financial performance. This article analyzes the performance of Bank Muamalat using a value chain analysis approach to understand its financing business processes from upstream to downstream. By mapping each stage of the process, this study identifies added value in each segment and weak points affecting the bank's financial performance. The analysis results indicate that the low profit generated from Bank Muamalat's financing activities indicates inefficiencies in one or more stages of the value chain. Limitations in expansion and efforts to attract new customers are among the factors influencing the bank's growth. Additionally, the suboptimal public perception of Islamic banking exacerbates this situation. Through value chain analysis, this study offers strategic insights for Bank Muamalat to improve the accessibility of its financing and funding products, both through physical and digital channels. This research adopts a qualitative approach with a case study methodology. In the context of the Islamic banking industry in Indonesia, PT Bank Muamalat Indonesia faces significant challenges, particularly in financing growth and contributing to company profits. This study adopts a case study approach to analyze the problems faced by the bank and provide relevant strategic recommendations. The analysis reveals several main challenges, including constraints in product development, human resource management, and technological infrastructure. Based on the findings, several recommendations are suggested, such as enhancing product research, integrating training into work schedules, and upgrading hardware. By adopting these solutions, Bank Muamalat is expected to improve operational efficiency, strengthen its market position, and achieve sustainable growth in the Islamic banking industry. Keywords: Islamic Banking, Bank Muamalat, Performance, Value Chain, Competitive Advantage.